2021
DOI: 10.1038/s42003-021-01704-2
|View full text |Cite
|
Sign up to set email alerts
|

CYK4 relaxes the bias in the off-axis motion by MKLP1 kinesin-6

Abstract: Centralspindlin, a complex of the MKLP1 kinesin-6 and CYK4 GAP subunits, plays key roles in metazoan cytokinesis. CYK4-binding to the long neck region of MKLP1 restricts the configuration of the two MKLP1 motor domains in the centralspindlin. However, it is unclear how the CYK4-binding modulates the interaction of MKLP1 with a microtubule. Here, we performed three-dimensional nanometry of a microbead coated with multiple MKLP1 molecules on a freely suspended microtubule. We found that beads driven by dimeric M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 65 publications
2
22
0
Order By: Relevance
“…Gliding motility assays, as well as motility assays on freely suspended microtubules, showed a counterclockwise rotation for the plus-end-directed motor protein kinesin-8 (Kip3) 36,40 , while another study found that kinesin-8 can switch protofilaments in both directions 38 . Several other motor proteins also exhibit rotational movements, including kinesin-1 33,39 , kinesin-2 35 , cytoplasmic dynein 37 , and kinesin-6 (MKLP1) 42 . However, in contrast to this large body of knowledge on chiral motor stepping in vitro , the role of motor proteins and their asymmetric stepping in the generation of torques within microtubule bundles in vivo and consequently spindle twist is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Gliding motility assays, as well as motility assays on freely suspended microtubules, showed a counterclockwise rotation for the plus-end-directed motor protein kinesin-8 (Kip3) 36,40 , while another study found that kinesin-8 can switch protofilaments in both directions 38 . Several other motor proteins also exhibit rotational movements, including kinesin-1 33,39 , kinesin-2 35 , cytoplasmic dynein 37 , and kinesin-6 (MKLP1) 42 . However, in contrast to this large body of knowledge on chiral motor stepping in vitro , the role of motor proteins and their asymmetric stepping in the generation of torques within microtubule bundles in vivo and consequently spindle twist is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies proposed that sideward stepping of kinesins and dynein allows them to bypass roadblocks on a microtubule [6][7][8]11,13,35 . We performed Monte Carlo simulations of bypassing of a roadblock with various multiple-motor motilities, especially changing the two parameters: the off-axis asymmetry, 𝛼𝛼 𝑌𝑌 , and the torque generation, 𝜃𝜃 step (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type kinesin-2 and -8, which have longer neck-linker domains than kinesin-1, and kinesin-6, which has an atypical neck region, do not track protofilaments. All these kinesins move towards microtubule plus ends along left-handed helical trajectories, as shown in a bead assay 6,11 , a microtubule surface-gliding assay 8,[11][12][13] , and a single-molecule tracking assay 8 . Furthermore, teams of non-processive dimeric kinesin-14 Ncd [14][15][16] , which moves towards microtubule minus…”
mentioning
confidence: 99%
See 2 more Smart Citations